Environmental Impact Assessment of the Restore Prototype - Alessandra-Diana Selejan-Ciubancan; Stefan Cristian Galusnyak; Letitia Petrescu; Calin-Cristian Cormos (Chemical Engineering Transactions)
The RESTORE concept aims to store energy by dehydrating copper sulphate when renewable electricity is available (e.g., in the summer when solar power is abundant) and rehydrating it when energy demand is higher (e.g., during winter when consumption rises and energy supplies are scarce). This study is focused on the RESTORE prototype, which combines the Organic Rankine Cycle (ORC)/Heat Pump (HP) with Thermochemical Energy Storage (TCES) technology. Life Cycle Assessment (LCA) was used to evaluate the environmental impact of this setup across specific spatial and temporal limits. Eight environmental KPIs were identified using the ReCiPe 2016 impact assessment method, with the LCA for Experts v.10.8 software utilized for the analysis. The generation of 30 kWh of thermal energy was set as the functional unit (FU) for the current study, with the system boundaries including the following: i) upstream processes—raw materials supply chains including Novec 649, CuSO4, oil production, as well as construction materials for the RESTORE components; ii) main processes—thermal energy charging and discharging cycles; and iii) downstream processes— wastewater treatment, recycling of CuSO4, Novec 649 and oil. The main impact categories were strongly affected by several subsystems, namely the production of copper that was utilized for producing CuSO4 and for the materials used in the RESTORE prototype construction. For example, HTPnon-cancer reached 75.48 kg 1.4-DB eq./h, while TETP summed 726.93 kg 1.4-DB eq./h. Regarding GWP, which stood at 12.15 kg CO2 eq./h, the most significant contributors were Novec 649 production and the energy charging cycle.